2017
DOI: 10.1007/s00105-017-3999-z
|View full text |Cite
|
Sign up to set email alerts
|

Evidenz der Kompressionstherapie

Abstract: There is a high level of evidence that compression therapy is effective to heal venous ulcers and to prevent recurrent ulcers. The use of compression bandages and hosiery after interventional and surgical procedures for varicose veins is based on experience but not on randomized controlled trials. According to clinical experience, the healing of inflammatory skin diseases (e.g., erythema nodosum, pyoderma gangrenosum, necrobiosis lipoidica, cutaneous leukocytoclastic vasculitis, and psoriasis of the extremitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
0
8
0
7
Order By: Relevance
“…Currently, no data exist on the effects of compression in lipoedema. However, studies in phlebology and sports medicine have shown that compression has an impressive effect on the inflammatory processes in subcutaneous tissue [51,52]. Confocal laser scanning microscopy has been used to show a significant reduction in pro-inflammatory cytokines and a simultaneous rise in anti-inflammatory mediators in the compressed tissue of patients with venous disease [53].…”
Section: Compression Therapymentioning
confidence: 99%
“…Currently, no data exist on the effects of compression in lipoedema. However, studies in phlebology and sports medicine have shown that compression has an impressive effect on the inflammatory processes in subcutaneous tissue [51,52]. Confocal laser scanning microscopy has been used to show a significant reduction in pro-inflammatory cytokines and a simultaneous rise in anti-inflammatory mediators in the compressed tissue of patients with venous disease [53].…”
Section: Compression Therapymentioning
confidence: 99%
“…Compressive bandages reduce the exudate and the inflammation and are particularly important during the inflammatory phase. There is some evidence that the compression reduces the inflammation in inflammatory ulcers such as PG and vasculitis 33 . NPWT can be used in the noninflammatory phase of PG to reduce the size of the lesion and to control the exudate 34 .…”
Section: Discussionmentioning
confidence: 99%
“…В таких случаях истина всегда находится где-то посередине. Так, большинство специалистов, активно практикующих склеротерапию, указывают на пользу 7-14-дневной компрессии и целесообразности ее пролонгации в зависимости от риска или появления нежелательных побочных явлений, таких как гиперпигментация и флебит [15][16][17].…”
Section: эстетическая флебологияunclassified